JUSTIFICATION OF THE STRUCTURE OF A SET OF MODELS FOR THE DEVELOPMENT AND IMPLEMENTATION OF REGIONAL PROGRAMS, TAKING INTO ACCOUNT ASSOCIATED RISKS - A. I. Denisova (Вестник университета)
The subject of the study is Federal programs of socio-economic development of the regions of the Russian Federation. The paper considers the computational and analytical tools for the development and implementation of support for development programs and shows the need for its improvement. The author presents the structure of the corresponding software in the form of a model complex for the formation and evaluation of regional development program options. The article gives the main indicators necessary for calculations. The study considers the methods of obtaining data for the formation, correction, and evaluation of the implementation of programs. The author proposes the scenario modeling apparatus as a tool for variable calculations to justify stable and satisfactory planning solutions. The article justifies the necessity of taking into account the impact of risks in the process of forming and implementing the program and proposes methods of their accounting. The paper proposes to use an ontological model for organizing the storage and presentation of information about the sources and consequences of risks.